Ecology, Diversity and Molecular Studies of Red Seaweed Gracilaria spp. in Lawas, Santubong and Asajaya, Sarawak - Muhammad Nur Arif, Othman (Universiti Malaysia Sarawak (UNIMAS), 2017)
Red seaweed Gracilaria (Gracilariaceae, Rhodophyta) is known as ‘Janggut Duyong’ by the local people of Sarawak, widely distributed in both temperate and tropical seawater zones. Gracilaria plays important roles as food materials and income for local people, provide protection and source of foods for diverse aquatic organisms, one of the primary producer in marine ecosystem and main contributor of agar worldwide. Despite the importance of Gracilaria in terms of ecology and socio-economy, little is known about Gracilaria species in Sarawak. Hence, this study was designed to: (i) assess selected water quality parameters in Gracilaria habitats, (ii) examine the abundance of Gracilaria in Lawas, Santubong and Asajaya, Sarawak as well as the aquatic organisms associated with it and (iii) identify species of Gracilaria using morphological characteristics and molecular approaches. Three field samplings were conducted in Lawas, Santubong and Asajaya from April 2013 to December 2014. Selected water quality was measured in-situ and ex-situ, whole thallus of Gracilaria and other aquatic organisms found within it were collected. Identification of Gracilaria using molecular analysis was done using cytochrome oxidase subunit 1 (CO1) gene marker. Four species of Gracilaria (Gracilaria blodgettii, G. changii, G. arcuata, G. coronopifolia) were identified based on morphological characteristics whereas only two species (G. blodgettii, Hydropuntia edulis) were found using molecular analysis. Both of the data were contradicted due to: (i) CO1 gene marker may not be suitable to resolve taxanomy of Gracilaria in Sarawak and (ii) high similarity in terms of morphology between G. coronopifolia and H. edulis. Other flora (Acanthophora sp. and Padina sp.) and fauna namely bivalves, polychaetes, shrimps, tunicates, small crabs and brittle stars were found living together in Gracilaria population. The water quality in Lawas and Santubong were under Class 2 of the Malaysian Marine Water Quality Criteria and Standard (MWQCS). In contrast, Asajaya’s water qualities fall under Class iv E of MWQCS. Overall, the values of water qualities recorded were within normal range of standard water quality for mangrove water and mariculture in Malaysia. Approximately 80% to 90% of the cage net in Lawas was covered by seaweeds and pH was the only parameter that show negative correlation with percentage cover of seaweeds (p= 0.000). In comparison, percentage cover of seaweeds in Santubong and Asajaya could not be determined due to regular collection by local people. Healthy population of Gracilaria could be easily found at all the sampling sites, thus they have the potential for future seaweed aquaculture. It is recommended that the state government agencies, Department of Fisheries Sarawak and other nongovernmental organisations to introduce and assist the local people embarking in seaweed culture